Work life balance: the experiences of black female academics at a university in Gauteng - Muthala, Mashudu Shadrack (My University, 2021)
Work-Life balance is becoming a priority among many institutions of higher learning across the globe. This is as employers realize the many benefits of having employees with balanced work and non-work domains. Consequently, this study sought to explore the experiences of black female academics regarding their work-life balance working at a university in Gauteng. This qualitative study followed an exploratory approach to consider the experiences of black female academics on their quest to achieve work-life balance. Ten respondents were purposively sampled to participate in the study. Semi-structured interviews were used to collect the necessary data. Thematic content analysis was used to analyze the collected data. The study revealed the following main findings: Firstly, Black female academics are confronted by both personal and professional challenges that hinder them from achieving a work-life balance. Identified personal challenges included family responsibilities, patriarchal and cultural practices. While work overload, lack of recognition and lack of respect by male senior colleagues were identified as work-related challenges. Secondly, unmarried Black female academics found it easier to strike a work-life balance compared to their married counterparts. This difference was attributed to the additional household duties that married participants are expected to carry out at home. Thirdly, many of Black female academics turn to religion to seek some sort of balance between their work and personal lives. It is envisaged that the findings will help in the development and implementation of strategies geared at enhancing the work-life balance of Black female academics working at various universities. More studies should be conducted to determine or examine how stages of life such as marriage, pregnancy, childbirth, and child rearing affect the performance of female academics at workplaces.
A research report submitted in partial fulfillment of the requirements for the degree Master of Arts in Occupational Social Work to the Faculty of Humanities, School of Human and Community Development, University of the Witwatersrand, 2021